Seraprevir and sofosbuvir for treatment of chronic hepatitis C virus infection: A single‐arm, open‐label, phase 3 trial. Issue 9 (2nd February 2021) - Kong, Fei; Wen, Xiaoyu; Wen, Xiaofeng; Wang, Xiaozhong; Wu, Guicheng; Lin, Shide; Wang, Li; Xing, Huichun; Yan, Xuebing; Zheng, Sujun; Ning, Qin; Wang, Zheng; et al.
Abstract: Background and Aim: This single‐arm, open‐label, multicenter, phase 3 trial evaluated the efficacy and safety of seraprevir, an hepatitis C virus (HCV) nonstructural protein 3/4A (NS3/4A) inhibitor, combined with sofosbuvir for treating Chinese patients with chronic HCV infection without cirrhosis. Methods: Treatment‐naive or interferon‐experienced adult patients without cirrhosis were treated with a universal, combinational regimen of seraprevir 100 mg, twice daily and sofosbuvir 400 mg, once daily, for 12 or 24 weeks. The primary efficacy endpoint was sustained virologic response at week 12 after treatment (SVR12). Results: Overall, 205 patients with genotype 1 HCV infection without cirrhosis were enrolled from 23 sites, 202 of whom completed the full treatment and post‐treatment course and 3 discontinued follow‐up. In total, 27 patients (13.2%) were interferon experienced. SVR12 was achieved by 201 out of 205 (98.0% [95% CI, 95.1%, 99.5%]) patients, 100.0% of patients with genotype 1a, and 98.0% of genotype 1b. In the other exploratory study, SVR 12 was achieved by 100% patients with genotype 2 ( n  = 21), genotype 3 ( n  = 7), and genotype 6 ( n  = 8). The majority of adverse events were mild to moderate and transient and did not require a specific medical intervention. Conclusions: The all‐oral, ribavirin‐free regimen of seraprevir and sofosbuvir is an effective and well‐tolerated treatment option for Chinese patients mono‐infected with HCV, including those with a history of interferon treatment.